Original paperDiabetes in patients with acute myocardial infarction treated with coronary angioplasty – influence on left ventricular systolic function on echocardiography - Tomaszuk-Kazberuk, Anna; Kożuch, Marcin; Bachórzewska-Gajewska, Hanna; Małyszko, Jolanta; Małyszko, Jacek; Kosacka, Urszula; Gościcka, Katarzyna; Dobrzycki, Sławomir; J. Musiał, Włodzimierz (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2010)
Introduction : Diabetes is associated with increased mortality after acute myocardial infarction (AMI) due to an increased incidence of post-infarction congestive heart failure. A relationship between diabetes and left ventricular (LV) systolic function could potentially explain this excess mortality. Aim : To assess the influence of diabetes on left ventricular systolic function on echocardiography in patients with AMI treated with coronary angioplasty. Materials and methods : Patients with AMI (n = 210, both STEMI and NSTEMI) treated with angioplasty were divided into 2 groups according to the presence of diabetes. LV systolic function was assessed using echocardiographic measurements (LV ejection fraction, left ventricular, left atrial, interventricular septum, posterior wall diameters). Segmental contractility was assessed using the wall motion index score. Results : We enrolled 210 patients, mean age 68 ±11 years (72 females). A previous diagnosis of DM was present in 26 (12.4%) patients, and 11 patients were classified as newly detected diabetics. Diabetics had significantly lower ejection fraction (EF) (43.2% vs. 46.1%, p = 0.045) and a tendency to thicker interventricular septum (12.8 mm vs. 11.9 mm, p = 0.07). Male patients with DM had a significantly bigger left ventricle than non-diabetics (54.2 ±4.7 mm vs. 50.7 ±6 mm, p = 0.011), thicker interventricular septum (13.5 ±2.5 mm vs. 12.0 ±1.7 mm, p = 0.001) and bigger left atrium (41.4 ±6.9 mm vs. 38.6 ±5.5 mm, p = 0.043). Women with diabetes had a tendency to thicker interventricular septum (12.5 ±1.9 mm vs. 11.5 ±2.0 mm, p = 0.056) and thicker posterior wall (11.4 ±1.6 mm vs. 10.5 ±1.6 mm, p = 0.028). Nevertheless, diabetics had significantly fewer akinetic segments than non-diabetics (2.6 ±1.7 vs. 3.9 ±2.6, p = 0.009). Conclusions : The presence of diabetes is associated with only selected echocardiographic parameters of impaired LV systolic function in the very early phase of acute myocardial infarction treated invasively.